Answer:
5 cm
Step-by-step explanation:
What you have there is an equilateral triangle. An equilateral triangle is a triangle that has sides with equal lengths and interior angles are equal as well. So if all angles are equal in a triangle, then that means that this is an equilateral triangle. So we can say that if one side of this triangle is 5cm
then the n would also be equal to 5cm.
10. The length of a side of a square is represented by (24 – 3x) feet. What is the
length of the side of the square when r = 6?
Answer:
The length of the side of the square is 6 feet.
Step-by-step explanation:
Given,
Length of side of square = [tex](24 - 3x)\ feet[/tex]
According to question, x = 6
So we have to substitute x with 6 in the given expression.
Length of side of square = [tex](24-3x)= 24-3\times6=24-18=6\ feet[/tex].
Thus the length of the side of the square is 6 feet.
Final answer:
To find the length of the side of the square when x is 6, substitute 6 for x into the given expression (24 - 3x). Thus, the length of the side is calculated as 6 feet.
Explanation:
The student asked for the length of the side of the square when x = 6. To find this, we substitute x with 6 into the expression representing the side length of the square, which is (24 - 3x) feet.
Replacing x with 6, we get:
(24 - 3The length of the side of the square when x is equal to 6 is therefore 6 feet.
3 and 5 over 8 minus 1 and 3 over 4
Answer:
Exact Form: 27/8
Decimal Form: 3.375
Mixed Number Form: 3 3/8
Step-by-step explanation:
3 + 5/8 - 1 + 3/4
I stared by making 5/8 a decimal
which is 0.625
then added 3 to 0.625 which is 3.625 then subtracted 1 which is 2.625
then i turned 3/4 to a decimal which is 0.75
i added 2.625 and 0.75
which is 3.375
Answer: 0
Step-by-step explanation:
3 and 5 over 8 minus 1 and 3 over 4
= 3 +5/8 - 1+3/4
= 8/8 - 4/4
=1 - 1
=0
population mean =72 and standard deviation =10, what is standard error of distribution of sample means for n=4 and n=25
Answer:
The standard error of distribution for n = 4 is 5 and for n = 25 is 2.
Step-by-step explanation:
1. Let's review the information given to us for solving the question:
Population mean = 72
Standard deviation = 10
Sample₁ = 4
Sample₂ = 25
2. For finding the standard error of the mean, we use the following formula:
Standard error = Standard deviation / √Size of the sample
Standard error for Sample₁ = 10/√4
Standard error for Sample₁ = 10/2 = 5
Now, let's find the standard error for Sample₂
Standard error for Sample₂ = 10/√25
Standard error for Sample₂ = 10/5 = 2
What is (g ° f)(2) for f(x) = 10/x -1 and g(x) = 7x - 4?
A) 0
B) 4
C) 10
D) 24
Answer:
The value of function (g o f) (2) is 24 . option D
Step-by-step explanation:
Given function as :
f(x) = [tex]\frac{10}{x}[/tex] - 1
And g(x) = 7 x - 4
So ,
(g o f) (x) = 7 ( [tex]\frac{10}{x}[/tex] - 1 ) - 4
Or, (g o f) (x) = [tex]\frac{70}{x}[/tex] - 7 - 4
Or, (g o f) (x) = [tex]\frac{70}{x}[/tex] - 11
So, For x = 2
I,e (g o f) (2) = [tex]\frac{70}{2}[/tex] - 11
Or, (g o f) (2) = 35 - 11
∴ (g o f) (2) = 24
Hence The value of function (g o f) (2) is 24 . Answer ( option D )
It’s question number 6, please help!
Answer:
a. s = 0.9r
not very sure about b
Step-by-step explanation:
I'll mark brainlest
find the distance between point A, (2,3) and point B, (-4,6) show your work by using the distance formula
Answer:
The distance is 7 (approximately).
Step-by-step explanation:
Given:
Point A, (2,3) and point B, (-4,6).
Now, to find the distance between the points using the formula:
Let A = (2,3) be [tex](x_{1}, y_{1})[/tex] and B = (-4,6) be [tex](x_{2}, y_{2})[/tex] and d = distance.
Putting the distance formula to find:
[tex]d=\sqrt{(x_{2}-x_{1})^{2} +(y_{2}-y_{1})^{2}}[/tex]
[tex]d=\sqrt{(-4-2)^{2} +(6-3)^{2}}[/tex]
[tex]d=\sqrt{(-6)^{2} +(3)^{2}}[/tex]
[tex]d=\sqrt{36 +9}[/tex]
[tex]d=\sqrt{45}[/tex]
[tex]d=6.71[/tex]
Distance = 6.71
Therefore, the distance is 7 (approximately).
Simplify square root of five times the quantity six minus four square root of three.
Answer:
C
[tex]6\sqrt{x} 5-4\sqrt{x} 15[/tex]
Answer:
6√5 - 4√3
Step-by-step explanation:
The question ask us to simplify the square root of 5 times the quantity 6 minus 4 square root of 3 . The word expression can be represented mathematically as follows:
√5 × 6 - 4√3 . The expression forms a Surd.
√5 × 6 - 4√3
6√5 - 4√3
Three-fourths of the students in the class did their homework last night. If 18 students in the class did their homework,
how many students are there in the class? Write an equation for this situation. Solve your equation algebraically two different ways.
Answer: 24 people are in the class
I am sorry I don’t know the equation but I hope this helps.
Step-by-step explanation:
3. 18. 18
- =. —. =. —-
4. ? 24
Y = -22x +9
y = 40x - 3
Answer:
x=6/31, y=147/31. (6/31, 147/31).
Step-by-step explanation:
y=-22x+9
y=40x-3
-----------------
-22x+9=40x-3
9=40x-(-22x)-3
9=40x+22x-3
9=62x-3
62x=9+3
62x=12
x=12/62
simplify,
x=6/31
-----------------
y=40(6/31)-3=240/31-3=240/31-93/31=147/31
x=6/31, y=147/31.
identify the transformation that carries the figure onto itself A) Reflect across the line Y=1 and rotate 990° clockwise about(-7,1) B) Reflect across the line Y=1 and rotate 1080° clockwise about (-7,1) C) Reflect across the line Y=1 and rotate 990° clockwise about (-7,1) D) Reflect across the line X=-6 and rotate 1080° clockwise about (-7,1)
Answer: The answer is B.
Step-by-step explanation:
Final answer:
The correct transformation that carries the figure onto itself is Option B: reflecting across the line y=1 and rotating 1080° clockwise about the point (-7,1), as the 1080° rotation is a multiple of 360° and does not change the figure's orientation.
Explanation:
The question is asking to identify the transformation that can be applied to a figure such that the figure maps onto itself. We're given various options that involve a reflection and a rotation. Reflection across a line like y=1 would flip the figure over this horizontal line. A rotation of 1080° clockwise about a point is equivalent to a full 360° rotation three times (since 1080° = 360° × 3), which would bring the figure back to its original position, effectively leaving it unchanged.
The correct answer is Option B, which includes a reflection across the line y=1 and a 1080° clockwise rotation about the point (-7,1). This is because the 1080° rotation, being an integer multiple of full circles, results in no net rotation, so the figure looks exactly the same after this operation. The reflection flips the figure across the line y=1 but, when combined with the rotation, it results in the figure mapping onto itself.
Options A and C suggest a 990° rotation, which is not a multiple of 360° and therefore would not result in the figure mapping onto itself. Option D suggests reflecting across the line x=-6, which is not in the given options for the reflection, and a 1080° rotation about the point (-7,1), which would rotate the figure back onto itself after the reflection, but the reflection line is incorrect.
If f(x) is the height, in cm, of a sunflower plant which is x days old, which of the
following statements best describes the meaning of f(60) = 210? (1 point)
1) The height of the sunflower plant is 60 cm when it is 210 days old.
2) The height of the sunflower plant is 210 cm when it is 60 days old.
3) The height of the sunflower plant is 210 cm when it is 3.5 days old.
0
4) The height of the sunflower plant is 60 cm when it is 3.5 days old.
Answer:
2) The height of the sunflower plant is 210 cm when it is 60 days old.
Step-by-step explanation:
Given:
The height of the sunflower plant is given by the value of the function [tex]f(x)[/tex] for a given value of 'x' and the age of the plant is given by [tex]x[/tex].
The expression is given as:
[tex]f(60)=210[/tex]
So, the 'x' value is 60 and the function value is 210.
So, the age of the plant is 60 days old. The height of the plant is 210 cm.
Thus, the above expression [tex]f(60)=210[/tex] means that the height of the sunflower plant is 210 cm when the plant is 60 days old.
So, from among all the choices given, only choice (2) defines it correctly.
Please help on this problem I don’t know how to do it and I’m getting tired of doing this
If it's Pythagorean Theorem, then use the following:
[tex]A^2 + B^2 = C^2[/tex]
You have to multiply the 2 values by themselves if you are trying to find the Hypotenuse, then you need to add those together, and then find the square root.
10 x 10 = 100
15 x 15 = 225
100 + 225 = 325.
[tex]\sqrt{325} = 18.0277564[/tex]
Answer: 18
Step-by-step explanation:
So this is referencing the Pythagorean theorem. It states that the two shorter sides squared, in your case 10 and 15, is equal to the longest side, or hypotenuse squared.
Step by step
1. Calculate both the shorter sides squared: 10*10= 100 and 15*15= 225
2. Add the 2 shorter sides: 100 + 225 = 325
3. Find the square root of 335: √(325) = 18.0277563773
4. Round to the nearest integer: 18
graph the line y = 2x - 5
Answer:
The Explanation is below with attachment.
Step-by-step explanation:
For the line y = 2x - 5
For Drawing a line on a graph we require minimum two points, but we will plot three points.
Here you can take any random value for X so that the corresponding Y value you will get.
So, put x = 0, in the equation we will get
[tex]y = 2(0) - 5\\\therefore y = -5\\\therefore Let\ A(0,-5)[/tex]
Similarly,
Put x = 1 we will get,
[tex]y= 2(1)-5\\\therefore y =-3\\\therefore Let\ B(1,-3)[/tex]
Again,
Put x = -1 we will get,
[tex]y= 2(-1)-5\\\therefore y =-7\\\therefore Let\ C(-1,-7)[/tex]
Now we have three points say point A (0,-5)), point B (1.-3) and point C (-1,-7)
See the graph below
The health club is raising money through a babysitting fundraiser. On Thursday, they charged $3 per hour plus an initial fee $40. On Friday, they charged $4 per hour plus an initial fee of $30. How many hours do they need to babysit to have the same money each day?
They need to babysit for 10 hours to have same money each day.
Step-by-step explanation:
On Thursday;
Charges = $3 per hour
Initial fee = $40
let x be the number of hours.
T(x) = 3x+40
On Friday;
Charges = $4 per hour
Initial fee = $30
F(x)= 4x+30
The cost will be same when;
T(x) = F(x)
[tex]3x+40=4x+30\\40-30=4x-3x\\10=x\\x=10[/tex]
They need to babysit for 10 hours to have same money each day.
Keywords: functions, addition
Learn more about functions at:
brainly.com/question/3071107brainly.com/question/3126500#LearnwithBrainly
Guys!! anyone can help me solve this geometry problem?
What is the area of this triangle?
Answer:
10657.5
Step-by-step explanation:
Long way that is unnecessarily long
We can start by finding the area of the larger triangle. Using the Pythagorean theorem, we can say that 251²-105²=the bottom side², and 251²-105²=51976, so the bottom side of the larger triangle is √51976 , or approximately 228. Then, the area of the larger triangle is √51976 * 105/2 = 11969 (approximately). Then, the area of the smallest triangle (the largest triangle - the one that we're trying to find the area of) is 105*(√51976-203)/2 = approximately 1312. Then, subtracting that from the total area, we get (√51976 * 105 - 105*(√51976-203))/2 = 105*203/2 = 10657.5
Short wayALTERNATIVELY, upon further review, we can just see that the height is 105 and the base is 203, so we multiply those two and divide by 2, as is the formula for the area of a triangle, to get 10657.5
A right triangle is shown below whose sides are 2x, x2 - 1, and x2 + 1.
(a)
Prove the identity (2x)2 + (x2 - 1)2 = (x2 + 1)2
for x > 1.
x2 +1
.12-1
Answer:
[tex](2x)^2 + (x^2 - 1)^2 = (x^2 + 1)^2[/tex] PROVED
Step-by-step explanation:
The sides of the given right triangle are : [tex]2x , (x^2 -1) , (x^2 +1)[/tex]
Now here, To show: [tex](2x)^2 + (x^2 - 1)^2 = (x^2 + 1)^2[/tex] .... (1)
Now, by ALGEBRAIC IDENTITY: [tex](a \pm b)^2 = a ^2 +b^2 \pm 2ab[/tex]
So here, similarly
[tex](x^2-1)^2 = (x^2)^2 + (1)^2 - 2 (x^2)\\(x^2+1)^2 = (x^2)^2 + (1)^2+ 2 (x^2)[/tex]
Now, substituting the value on Left side of (1) , we get :
[tex](2x)^2 + (x^2 - 1)^2 = 4x^2 + (x^2)^2 + (1)^2 - 2 (x^2) = 4x^2 + (x^4) + 1 - 2 x^2 = x^4 + 1 + 2x^2[/tex] ...... (a)
Also, the right side of (1) is:
[tex](x^2 + 1)^2 = (x^2)^2 + (1)^2+ 2 (x^2) = x^4 + 1 + 2x^2[/tex] ... (b)
from(a) and (b) we see that
[tex]x^4 + 1 + 2x^2 = x^4 + 1 + 2x^2\\\implies(2x)^2 + (x^2 - 1)^2 = (x^2 + 1)^2[/tex]
HENCE PROVED.
Women's swinsuit are 75% off at the end of the summer seson how much will a customer save by buying an $80 swimsuit while it is on sale.
Explain why...
Answer:
$60
Step-by-step explanation:
75% divided by 100 x 80 = 60
OR
$80 divided by 100 x 75 = 60
Evaluate g(x) = x – 13 over the domain {2, 4, 6, 8). What is the range of g(x)2
Answer:
The range of g(x) = {-11,-9,-7,-5}.
Step-by-step explanation:
Given:
g(x) = x – 13 over the domain {2, 4, 6, 8).
Now, to evaluate:
Putting [tex]x=2[/tex]
[tex]g(2)=2-13=-11[/tex]
Putting [tex]x=4[/tex]
[tex]g(4)=4-13=-9[/tex]
Putting[tex]x=6[/tex]
[tex]g(6)=6-13=-7[/tex]
Putting [tex]x=8[/tex]
[tex]g(8)=8-13=-5[/tex]
So, the range is {-11,-9,-7,-5}.
Therefore, the range of g(x) = {-11,-9,-7,-5}.
What is the molar mass dinitrogen monoxide?
The molar mass of dinitrogen monoxide?
Is=N2O=(14×2)+16
=44g/mol
Final answer:
The molar mass of dinitrogen monoxide (N₂O) is 44.02 g/mol, calculated by adding the atomic masses of two nitrogen atoms (14.01 g/mol each) and one oxygen atom (16.00 g/mol).
Explanation:
The molar mass of dinitrogen monoxide, which is chemically denoted as N₂O, can be calculated by adding together the atomic mass of nitrogen with the atomic mass of oxygen. Nitrogen (N) has an atomic mass of approximately 14.01 g/mol, and since we have two nitrogen atoms, we multiply this by 2. Oxygen (O) has an atomic mass of about 16.00 g/mol. Therefore, the molar mass of dinitrogen monoxide is:
(14.01 g/mol × 2) + (16.00 g/mol × 1) = 28.02 g/mol + 16.00 g/mol = 44.02 g/mol.
This value represents the weight of one mole of dinitrogen monoxide molecules. The importance of knowing the molar mass of a compound like dinitrogen monoxide relates to the calculations involved in chemical reactions and stoichiometry, specifically when dealing with gases under various conditions of temperature and pressure.
i need help asap :(
Answer:
D
Step-by-step explanation:
Firstly, perpendicular line has a slope that is "negative reciprocal" of the given line's slope.
The equation of a line is y = mx + b
Where m is the slope and b is the y-intercept
So, the given line has a slope of "-4", hence the perpendicular line would have a slope of "1/4". So immediately we can eliminate Answer Choice "A".
Now, let's see which of the other choices is our correct answer. Since we know this line has slope of "1/4", we can write:
y = (1/4)x + b
Given the point (4,5), we can replace "x" with "4" and "y" with 5 and find b:
[tex]y=\frac{1}{4}x+b\\5=\frac{1}{4}(4)+b\\5=1+b\\b=5-1\\b=4[/tex]
So, the equation is:
[tex]y=\frac{1}{4}x+4[/tex]
Correct answer is D
Mauna Loa depresses the sea floor, resulting in 26400 more feet added to its height. If Mauna Loa is 13700 ft tall. What is the total height of Mauna Loa?
Answer:40100 feet
Step-by-step explanation:26400 +13700 = 40100
The total height of Mauna Loa is by summation 26400 +13700 = 40100 feet.
What is summation?A summation, abbreviated as a sum, is the outcome of adding two or more numbers or quantities. Here are always an integer number of terms in a summation. There could be only two terms, but there could be one hundred, a thousand, or a million.
As per the given,
Initial height = 13700 feet
Height add on = 26400 feet
Total height = 13700 feet + 26400 feet = 40100 feet
Hence "The total height of Mauna Loa is by summation 26400 +13700 = 40100 feet".
For more information about summation
brainly.com/question/10777222
#SPJ2
what is x^2+4=0 over the set of complex numbers?
[tex]\bf x^2+4=0\implies x^2=-4\implies x = \pm\sqrt{-4}\implies x = \pm\sqrt{-1\cdot 2^2} \\\\\\ x = \pm\sqrt{-1}\cdot \sqrt{2^2}\implies x = \pm 2i[/tex]
Please help I need this paper finished by tonight please help
Step-by-step explanation:
Multiply the Fraquetions 277/160 3 right so Multiply the numerator and[tex] \frac{277}{160 \sqrt{3 } } [/tex]denominator separately
[tex]277 \sqrt{3} [/tex]
the below 160 Number 2) Same thing with the first one Multiply the Fraquetions, then multiply the numerator and denominator separately so
[tex] \frac{590}{160} \sqrt{17} [/tex]
then change to
[tex]590 \sqrt{17} [/tex]
the below that is a 5 and above it on the top right corner out 160
24/2=_/3=_/5.5=108/_=_/15
Answer:
The answer is 24/2=36/3=66/5.5=108/9=180/15.
Step-by-step explanation:
Given:
24/2=_/3=_/5.5=108/_=_/15.
Now, we need to solve this by putting [tex]x[/tex] in the place of _ and then continue:
[tex]\frac{24}{2} =\frac{x}{3}[/tex]
By cross multiplication we get:
[tex]72=2x[/tex]
By dividing with 2 we get:
[tex]36=x[/tex]
Now, we will continue like this process:
[tex]\frac{36}{3}=\frac{x}{5.5}[/tex]
[tex]198=3x[/tex]
[tex]x=66[/tex]
And, then again:
[tex]\frac{66}{5.5}=\frac{108}{x}[/tex]
[tex]66x=594[/tex]
[tex]x=9[/tex]
And, last:
[tex]\frac{108}{9}=\frac{x}{15}[/tex]
[tex]9x=1620[/tex]
[tex]x=180[/tex]
Therefore, the answer is 24/2=36/3=66/5.5=108/9=180/15.
Sarah wrote two decimals on the chalkboard. The decimals she wrote were were 5.73 and -6.1. What is the sum of the two decimals Sarah wrote?
Answer:
-0.37
Step-by-step explanation:
Given that a rectangle has a length of
5/
2
x + 10 with a width of
5/
2
x + 5, which expression represents the area of the rectangle?
Answer:
A=(5/2x+10)(5/2x+5)
Step-by-step explanation:
A=LW
A=(5/2x+10)(5/2x+5)
Haley invests $16,820 in a nine-year CD bearing 5.8% interest, and $21,950 in an online savings account giving 3.0% interest. When the CD reaches maturity, how much more interest will it have generated than the savings account?
Answer:
$2853.5
Step-by-step explanation:
Let us assume that the interest rate of both the investments of Haley is simple interest.
So, $16820 amounts of investment in nine-year CD bearing 5.8% interest will get interest of [tex]16820 \times \frac{5.8}{100} \times 9 = 8780[/tex] dollars.
Again, $21950 amounts of investment in an online savings account giving 3% interest will give interest of [tex]21950 \times \frac{3}{100} \times 9 = 5926.5[/tex] dollars.
Therefore, the nine-year CD will give more interest by $(8780 - 5926.5) = $2853.5. (Answer)
Answer:
C. $2,853.54
Step-by-step explanation:
I just answered it correct
Order the numbers from greatest to least.
36, 36.10, 36.01,37
Answer:
36.10, 36, 36.01,37
Step-by-step explanatoion:
Answer:
36 , 36.01 , 36.1 , 37
Step-by-step explanation:
Add. 1/2+(−3/5) Enter your answer as a fraction, in simplified form, in the box.
Answer:
-1/10
Step-by-step explanation:
1/2 - 3/5
Find common denominator. in this case, it'll be 10
1/2 * 5/5 = 5/10
3/5 * 2/2 = 6/10
5/10 - 6/10 = -1/10
A pet store specializes in exotic fish. The graph shows a proportional relationship between the number of fish and the number of fish tanks at the store.
Answer:
could you please take a screen shot please?
Step-by-step explanation:
Answer:
13
Step-by-step explanation:
if there are 5 tanks and 65 fish in all the tanks together, you take 65 and divide it by 5 to get 13 fish in each tank